Impact of interference effects on Higgs-boson searches in the di-top final state at the LHC - Bahl, Henning; Kumar, Romal; Weiglein, Georg (Journal of high energy physics, 2025)
The di-top final state is an important search channel for additional Higgs bosons at the LHC. In this channel, large signal-background interference contributions can strongly distort a resonance peak as it would be expected from a pure signal contribution. Moreover, signal-signal interference effects can have a significant impact if more than one additional scalar particle is present. In this work, we perform a comprehensive model-independent analysis of the various interference contributions considering two additional heavy scalars that can mix with each other. We point out the importance of taking into account loop-level mixing between the scalars. A proper treatment of these mixing effects, which has not been previously carried out for the di-top final state, introduces additional relative phases between different parts of the amplitudes entering the interference contributions which we find to have a strong impact on the di-top invariant mass distribution. We study the interference effects both in an idealistic setting as well as taking into account experimental limitations using Monte-Carlo simulations. We demonstrate that the emerging experimental signatures can be unexpected and difficult to interpret. In particular, we point out that an experimental signature manifesting itself as an excess near the tt̄ threshold may actually be caused by new scalar particles with much higher masses. We comment in this context on the recent excess that has been observed by the CMS collaboration near the tt̄ threshold in their searches in the di-top final state.